Impact of agricultural cooperatives on the food security status of households in Oromia regional state, Ethiopia: The case of Halu Woreda - Amanuel Kussia; Lensa Tekalign Ifa (Cogent Economics & Finance, 2023)
Agricultural cooperatives are considered as an institutional instrument for supporting smallholder farmers and contributing to poverty alleviation and food security. However, empirical literature and practices on the ground are mixed and inconclusive. The main purpose of this study is, therefore, to analyze the impact of agricultural cooperatives on households' food security status in the context of Halu Woreda. The study employed a quasi-experimental research design to estimate the impact of such collective organizations on food security. Primary data were collected from 260 rural households drawn via a stratified random sampling technique. A variety of impact estimation models were employed to check the robustness of the results. The findings revealed that being a cooperative member is determined by a combination of factors, including the sex and age of the household head; access to farm inputs, credit, and training; and the welfare status of the household head. The findings also showed that agricultural cooperatives have a statistically significant positive impact on the food security status of households. It is concluded that agricultural cooperatives are effective in improving the food security status of the households in the study area. Therefore, regional rural development policy and strategy should focus on strengthening and genuinely supporting the existing agricultural cooperatives while encouraging the establishment of new ones through an inclusive approach in ways that directly address poverty and food insecurity. By highlighting the implications of the impact of agricultural cooperatives on food security, this article contributes to the ongoing debates on the potential benefits of such associations to farmers' livelihoods in rural areas.
Keywords: 330; agricultural cooperatives; endogenous switching regression; food security; household food balance model; Oromia; propensity score matching